The genome sequence of the dark-edged bee fly, Bombylius major (Linnaeus, 1758) [version 1; peer review: 2 approved] - Erica McAlister; Mara K.N. Lawniczak; Liam M. Crowley (Wellcome Open Research, 2023)
We present a genome assembly from an individual male Bombylius major (the dark-edged bee fly; Arthropoda; Insecta; Diptera; Bombyliidae). The genome sequence is 304.3 megabases in span. The whole assembly is scaffolded into 7 chromosomal pseudomolecules, including the X and Y sex chromosomes. The mitochondrial genome has also been assembled and is 17.8 kilobases in length. Gene annotation of this assembly on Ensembl identified 10,852 protein coding genes.